Characterization of the diet of Brycon hilarii Valenciennes, 1850 (Characiformes, Characidae) related to the hydrological and floodable forest of the North Pantanal, Taiamã Ecological Station (Research, Society and Development, 2021)
Pantanal is one of the largest humid areas in the world, characterized by changes during hydrological cycles, which correspond to periods that alternate during floods and ebbs. This study aimed to analyze the diet of Brycon hilarii (Valenciennes, 1850) in different hydrological periods of the Ecological Station of Taiamã in Mato Grosso, Brazil, a conservation unit of worldwide interest, and its relationship with the formation of vegetation. Were 353 specimens captured in monthly campaigns, during the four hydrological periods, from August 2013 to July 2015, then packed in thermal boxes and sent to the laboratory, where the biometric data and stomach removal were noted for analyzes of food importance (IAi). The results show that Erytrhina fusca Lour. (squash) is the main food item in the B. hilarii diet. During the flood periods, it had an IAi of 95% and at flood 60%. Furthermore, B. hilarii proved to be a generalist in feeding on E. fusca during periods of high, low and dry periods, being a specialist in the period of flood. According to the size of the specimen the volume of intact and crushed seeds in relation to the standard size, it was found that the seeds are ingested according to the size according to the size of the specimen. This fact contributes to the importance of hydrological periods, together with the E. fusca monodominance in the place, which provides an increase in food resources for B. hilarii, through strategies, coinciding with the greater availability of E. fusca in this environment.